(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper reviews various researchers’ perspective on project planning applications and management role in the construction industry worldwide. Initially introduction to the concept is done in brief and later literature review has been carried out specifically focusing on management aspects and front end project planning aspects in construction industry. The construction industries now days have developed very rapidly. The growth of the industry leads to competition, and hence the need of the time is to plan properly the business and to have proper management.